USULAN PENINGKATAN KEPUASAN KONSUMEN BERDASARKAN METODE SERVICE QUALITY DI CULTURE BARBERSHOP CABANG UJUNG BERUNG BANDUNG - HUDIYA, HAFFIYAN FAZA; IRIANTI, LAUDITTA (e-Proceeding FTI, 2024)
XYZ barbershop has problems regarding customer satisfaction because there are complaints addressed to management. This study aims to provide proposals to improve Service Quality at XYZ barbershop Ujung Berung branch using the Service Quality (SERVQUAL) method. The measurement was carried out through the distribution of questionnaires to 97 respondents. The results of data processing analysis on Gap 5 are negative caused by Gap 1 and Gap 2. Uproposal of improvement is made based on the cause of dissatisfaction. Proposed improvements include increasing management perceptions in XYZ barbershop aimed at management, work instructions and improving SOPs while working. The proposal will be implemented for one month from November 29, 2023 to December 29, 2023, and after completion data will be collected to process whether there is a quality improvement based on the calculation of Gap 5 on each attribute. The implementation results show a reduction in the amount of dissatisfaction, from the beginning there are 11 attributes now to four attributes increased in several attributes after implementation, as can be seen from the processing of Gap 5 data after implementation. Abstrak XYZ barbershop memiliki permasalahan perihal kepuasan konsumen karena terdapat komplain yang ditujukan kepada manajemen. Penelitian ini bertujuan memberikan usulan untuk meningkatkan kualitas pelayanan di XYZ barbershop cabang Ujung Berung menggunakan metode Service Quality (SERVQUAL). Pengukuran dilakukan melalui penyebaran kuesioner kepada 97 responden. Hasil analisis pengolahan data pada Gap 5 negatif disebabkan oleh Gap 1 dan Gap 2. Usulan perbaikan dibuat berdasarkan penyebabnya ketidakpuasan. Usulan perbaikan diantaranya menaikkan persepsi manajemen di XYZ barbershop yang ditujukan kepada manajemen, instruksi kerja dan perbaikan SOP saat bekerja. Usulan akan diimplementasikan selama satu bulan sejak tanggal 29 November 2023 hingga 29 Desember 2023, dan setelah selesai data akan dikumpulkan untuk diolah apakah terdapat peningkatan kualitas berdasarkan perhitungan Gap 5 pada setiap atribut. Hasil implementasi menunjukkan adanya pengurangan jumlah ketidakpuasan, dari awal terdapat 11 atribut sekarang menjadi empat atributpeningkatan pada beberapa atribut setelah implementasi, seperti terlihat dari pengolahan data Gap 5 setelah implementasi.